(untitled) (European Journal of Pure and Applied Mathematics, 2025)
A new class of continuous multifunctions between an ideal topological space and a bitopological space, called upper (lower) τ^α(σ_1,σ_2)-continuous multifunctions, has been defined and studied. Moreover, several characterizations and some properties concerning upper τ^α(σ_1,σ_2)-continuous multifunctions and lower τ^α(σ_1,σ_2)-continuous multifunctions are established.